Factors Associated with Providing Complementary Food for ASI (MP-ASI) Too Early in Sifaoroasi Village South Nias Regency in 2022 - Purnama Handayani (Sean Institute, 2023)
Complementary Foods for Mother's Milk (MP-ASI) are foods or drinks containing substances that are given to infants or children aged 6-24 months. The provision of MP-ASI has not been achieved which is influenced by several factors such as knowledge, mother's health and occupation, MP-ASI advertising, health workers, culture and socio-economics. This study aims to determine the factors associated with the provision of complementary feeding (MP-ASI) too early in Sifaoroasi Village, South Nias Regency in 2022. This research is a quantitative research with cross sectional approach. This research was conducted from September 12, 2022 to September 24, 2022. The population is 24 people. Sampling using total sampling with a total sample of 24 people. Data processing starts from editing, coding, tabulating, entry and data processing. Data analysis using chi-square test The results showed that the age factor with a value of p = 0.208 > a = 0.05, the education factor with a value of p = 0.839 > a = 0.05 and the work factor with a value of p = 0.883 > a = 0.05. While the parity factor with a value of p = 0.001 > a = 0.05, knowledge with a value of p = 0.004 > a = 0.05 and the attitude factor with a value of p = 0.007 > a = 0.05. So it can be concluded that the parity factor, knowledge and attitude related to the provision of complementary feeding (MP-ASI) too early, while the maternal characteristics factor was not related to the provision of complementary feeding (MP-ASI) too early.